2008
DOI: 10.1007/s11060-008-9716-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cognitive follow-up in primary CNS lymphoma patients treated with chemotherapy and reduced-dose radiotherapy

Abstract: High-dose chemotherapy and whole brain radiotherapy (WBRT) can prolong survival in primary CNS lymphoma (PCNSL) patients, but is often associated with clinically significant cognitive decline. In this study we assessed neuropsychological functioning prospectively in newly diagnosed PCNSL patients treated with induction chemotherapy followed by reduced-dose WBRT. Twelve patients underwent neuropsychological evaluations at diagnosis, after induction chemotherapy, and 6 and 12 months after WBRT. Nine patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 29 publications
1
59
1
2
Order By: Relevance
“…33 Follow-up of a small number of patients indicates no significant cognitive decline up to 24 months after reduced-dose WBRT; however, difficulties in verbal memory and motor speed have persisted during ongoing follow-up. 34 In our report, there were no differences among the 3 non-WBRT groups in any outcome measure. Of interest, 8 (12%) of 65 survivors treated with chemotherapy without WBRT showed cognitive impairment in multiple domains even after complete disease remission.…”
Section: Statistical Analysis Clinical and Demographic Characteristicscontrasting
confidence: 48%
“…33 Follow-up of a small number of patients indicates no significant cognitive decline up to 24 months after reduced-dose WBRT; however, difficulties in verbal memory and motor speed have persisted during ongoing follow-up. 34 In our report, there were no differences among the 3 non-WBRT groups in any outcome measure. Of interest, 8 (12%) of 65 survivors treated with chemotherapy without WBRT showed cognitive impairment in multiple domains even after complete disease remission.…”
Section: Statistical Analysis Clinical and Demographic Characteristicscontrasting
confidence: 48%
“…Two recent studies suggested that WBRT dose reduction to 23-30 Gy in patients in CR after chemotherapy is associated with similar outcomes to receiving higher radiation doses, with better neurotolerability. 83,84 These observations deserve to be addressed in multicenter prospective trials, with standardized neuropsychologic assessment.…”
Section: Is Consolidation Radiotherapy Really Needed?mentioning
confidence: 99%
“…Correa and colleagues investigated a modified treatment regimen consisting of methotrexate-based chemotherapy incorporating rituximab, a chimeric monoclonal antibody, and reduced-dose WBRT aimed at improving efficacy and decreasing neurotoxicity in primary CNS lymphoma patients in a prospective, uncontrolled study [50]. Of the 19 patients with primary CNS lymphoma, 12 completed neuropsychological assessments at diagnosis, after induction chemotherapy and prior to reduced-dose WBRT and consolidation chemotherapy, and approximately 6 and 12 months after treatment.…”
Section: Reviewmentioning
confidence: 99%